Diagnostic Approach to Hepatitis B Virus (HBV) Infection - Te, MD, Helen S. (North American Journal of Medicine and Science, 2011)
Hepatitis B infection is a global health problem, leading to cirrhosis and hepatocellular carcinoma in some patients and accounting for 6,000 deaths annually. The diagnosis of HBV infection is based largely on the interpretation of serologic markers and hepatitis B DNA levels, which allows establishment of the phase of infection and provides the groundwork for management strategies. More recently, genotyping and detection of genetic mutations that confer drug resistance provide additional data that assist in the therapeutic decisions. Histologic staging also presents important information that allows for individualized management of the disease. This paper reviews the various tests utilized in the diagnosis of HBV infection and their roles in the identification of the different phases of infection and in the determination of the need for further management.